Trauma Culture : The Politics of Terror and Loss in Media and Literature - Kaplan, E. Ann (Book collections on Project MUSE., 2005)
It may be said that every trauma is two traumas or ten thousand-depending on the number of people involved. How one experiences and reacts to an event is unique and depends largely on one's direct or indirect positioning, personal psychic history, and individual memories. But equally important to the experience of trauma are the broader political and cultural contexts within which a catastrophe takes place and how it is "managed" by institutional forces, including the media. In Trauma Culture, E. Ann Kaplan explores the relationship between the impact of trauma on individuals.